Analysis of rainfall prediction using machine learning data mining and satellite techniques - B.Shardoor, Nikhilkumar; Venkateswar Rao, Mandapati (International Journal of Engineering and Technology, 2018)
In the era of big data, finding a solution from the huge data is a very big challenge. The buzz word Analytics which helps us in solving such problems, Data analytics is composed of various statistical and analytical methods used to develop new techniques to predict future possibilities. In the current scenario forecasting the rainfall is measured to be an important and thought-provoking task, as itâ€™s closely associated with the agriculture, economy and human life. Accuracy of a rainfall forecasting has importance for countries like India whose economy is majorly depends on agriculture. The rainfall prediction is to predict the state of current weather condition. The weather is a dynamic in nature, statistical tech-niques are unsuccessful to provide thee decent accuracy of rainfall. This survey paper provides a different approaches like, Machine Learning, Data Mining and Satellite forecastingâ€™s Techniques and their Algorithms are being used and analyzed in getting the better accuracy of rainfall. The comparative study helps experts and non-experts in understanding which method can gives better accuracy of rainfall prediction.Â Â